Application of indicator kriging to the complementary use of bioindicators at three trophic levels. (Environmental pollution (Barking, Essex : 1987), 2009)
The use of biological indicators is widespread in environmental monitoring, although it has long been recognised that each bioindicator is generally associated with a range of potential limitations and shortcomings. To circumvent this problem, this study adopted the complementary use of bioindicators representing different trophic levels and providing different type of information, in an innovative approach to integrate knowledge and to estimate the overall health state of ecosystems. The approach is illustrated using mercury contamination in primary producers (mosses), primary consumers (domestic pigeons and red-legged partridges) and top predators (Bonelli's eagles) in southern Portugal. Indicator kriging geostatistics was used to identify the areas where mercury concentration was higher than the median for each species, and to produce an index that combines mercury contamination across trophic levels. Spatial patterns of mercury contamination were consistent across species. The combined index provided a new level of information useful in incorporating measures of overall environmental contamination into pollution studies.

Application of indicator kriging to the complementary use of bioindicators at three trophic levels. - Figueira, Rui; Tavares, Paula C.; Palma, Luís; Beja, Pedro; Sérgio, Cecília (Environmental pollution (Barking, Essex : 1987), 2009)
The use of biological indicators is widespread in environmental monitoring, although it has long been recognised that each bioindicator is generally associated with a range of potential limitations and shortcomings. To circumvent this problem, this study adopted the complementary use of bioindicators representing different trophic levels and providing different type of information, in an innovative approach to integrate knowledge and to estimate the overall health state of ecosystems. The approach is illustrated using mercury contamination in primary producers (mosses), primary consumers (domestic pigeons and red-legged partridges) and top predators (Bonelli's eagles) in southern Portugal. Indicator kriging geostatistics was used to identify the areas where mercury concentration was higher than the median for each species, and to produce an index that combines mercury contamination across trophic levels. Spatial patterns of mercury contamination were consistent across species. The combined index provided a new level of information useful in incorporating measures of overall environmental contamination into pollution studies.
The following values have no corresponding Zotero field: accession-num: 19477568
Keywords: Animals; Bioindicators; birds; Birds: metabolism; Bryophyta; Bryophyta: chemistry; Bryophyta: metabolism; Ecosystem; Environmental Monitoring; Environmental Monitoring: instrumentation; Environmental Monitoring: methods; Environmental Monitoring: statistics & numerical d; Environmental Pollutants; Environmental Pollutants: analysis; Environmental Pollutants: metabolism; Feathers; Feathers: chemistry; Feathers: metabolism; Indicator kriging; Indices; Mercury; Mercury: analysis; Mercury: metabolism; Models; Mosses; Portugal; Statistical